Measurement of the ratio of the production cross sections times branching fractions of Bc± → J/ψπ± and B± → J/ψK± and B(Bc± → J/ψπ±π±π∓)/B(Bc± → J/ψπ±) in pp collisions at √s=7 Tev - Khachatryan, V.; Sirunyan, A. M.; Tumasyan, A.; Adam, W.; Bergauer, T.; Dragicevic, M.; Eroe, J.; Fabjan, C.; Friedl, M.; Fruehwirth, R.; Ghete, V. M.; Hartl, C.; et al. (SPRINGER, 2015)
The ratio of the production cross sections times branching fractions (sigma(B-c(+/-))B(B-c(+/-) -> J/psi pi(+/-)))/(sigma(B-+/-)B(B-+/- -> J/psi K-+/-)) is studied in proton-proton collisions at a center-of-mass energy of 7TeV with the CMS detector at the LHC. The kinematic region investigated requires B-c(+/-) and B-+/- mesons with transverse momentum p(T) > 15 GeV and rapidity vertical bar y vertical bar J/psi pi(+/-)pi(+/-)pi(-/+) decay is also observed in the same data sample. Using a model-independent method developed to measure the efficiency given the presence of resonant behaviour in the three-pion system, the ratio of the branching fractions B-c(+/-) -> J/psi pi(+/-)pi(+/-)pi(-/+)/B(B-c(+/-) -> J/psi pi(+/-)) is measured to be 2.55 +/- 0.80 (stat) +/- 0.33 (syst)(-0.01)(+0.04) (tau(Bc)), consistent with the previous LHCb result.
Keywords: Hadron-Hadron Scattering; Branching fraction; B physics; SIMULATION; GENERATOR; BCVEGPY; Physics